Where's the data to support educators' data use for instructional practice?. Issue 3 (3rd July 2022) - Barnes, Nicole; Brighton, Catherine M.; Fives, Helenrose; Meyers, Coby; Moon, Tonya R.
ABSTRACT: Data use has gained policy traction at the federal, state, and local levels in the United States and internationally, and is now embedded in teacher, principal, and district leader standards in the U.S. However, many decisions implemented in policy and practice are being made on insufficient evidence and assume a relatively straightforward, intuitive, and coherent data use process in which educators have access to data; the data are appropriate for the task at hand; and that they have the skills to retrieve, analyze, and respond appropriately to directly or indirectly change instruction for the better. Yet, research indicates that in actuality the practice of educator data use is complicated and heavily influenced by both organizational and individual factors such as school leaders' influence on teachers' data use, and teachers' beliefs about, capacity for, and use of data for instructional decisions. Because we and many others in the field of education have come to see the potential value and utility of data use by educators, we offer the five recommendations to improve educators' data use for instructional practice.